2013
DOI: 10.7717/peerj.45
|View full text |Cite
|
Sign up to set email alerts
|

Does haemosporidian infection affect hematological and biochemical profiles of the endangered Black-fronted piping-guan (Aburria jacutinga)?

Abstract: Infectious diseases can cause deleterious effects on bird species, leading to population decline and extinction. Haemosporidia can be recognized by their negative effects on host fitness, including reproductive success and immune responses. In captivity, outbreaks of haemosporidian infection have been observed in birds in zoos and aviaries. The endemic Brazilian Atlantic rainforest species Aburria jacutinga is one of the most endangered species in the Cracidae family, and wild populations of this species are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
18
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 54 publications
6
18
3
1
Order By: Relevance
“…lineage described here (Motta et al, 2013). However, there were no significant alterations in hematological, biochemical and in the serum protein (albumin and immunoglobulins) profiles due to this infection, indicating that this parasite may not cause major deleterious effects under the same captive circumstances as evaluated here.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…lineage described here (Motta et al, 2013). However, there were no significant alterations in hematological, biochemical and in the serum protein (albumin and immunoglobulins) profiles due to this infection, indicating that this parasite may not cause major deleterious effects under the same captive circumstances as evaluated here.…”
Section: Discussionsupporting
confidence: 56%
“…Birds in our study and in Motta et al (2013) showed low parasitemia (ranging from undetectable parasites under microscopy to 0.1%), a characteristic of the chronic stage of infection (Valkiūnas, 2005). These birds were provided with food and water, and were protected from harsh environmental conditions and predators.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Species of this mosquito genus are the main vectors of avian Plasmodium [7] and for this reason Culex was included in our analysis despite the lack of identification to the species level. There are no confirmed cases of natural transmission of Plasmodium gallinaceum outside of the Asian continent [3], but lineages closely related to this parasite have been detected in wild birds from southeastern Brazil [10] and in captive Aburria jacutinga , a bird of the order Galliformes [43]. We mist-netted birds for haemosporidian studies at these same areas and periods, but no P. gallinaceum -like parasites were detected (Ferreira Jr., unpublished observations).…”
Section: Discussionmentioning
confidence: 99%